Management and Outcomes of Wilson Disease in Pregnancy: A Case Report - Zahra Moaazeni; Danial Soltani; Mahnaz Boroumand Rezazadeh; Mohammad Reza Rouhbakhsh Zahmatkesh; Neda Davaryari (Case Reports in Clinical Practice, 2023)
Pregnancy in a woman with Wilson disease (WD) can cause pre-eclampsia, miscarriage, and preterm labor and causes hepatic, neurologic, and hematologic complications aside from pregnancy-related difficulties. A 30-year-old female was brought to the emergency room (ER) in her 38th gestational week (GW) with the chief complaint of left foot swelling and weight gain. Aside from a platelet count of about 73000, the rest of the assessment and findings were normal. Regarding the reassurance of the platelet count and holding the medical treatment, throughout the vaginal delivery, a child with Apgar of 9-10 was delivered. WD in pregnancy tends to have complications, thus patient management and how the patient is treated are critical.